Strategy for the Effectiveness of the Implementation of Academic Information Systems in College in Efforts to Improve Information Quality - Awan Setiawan; Iman Sudirman; Nurman Helmi; Erwin Yulianto; Ruhanda, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The success of information systems research has begun to decline in the past few years, but existing research is still inaccurate in its definition and in the factors that affect the success of the information system. The purpose of this research is to find out, study, and analyze the effectiveness of implementing academic information systems in universities to improve the quality of information. The research was conducted using a qualitative approach and case studies, namely problem formulation, study proposition, analysis unit, data linkage to the proposition, the criteria for interpreting the findings, and making conclusions and recommendations. From the results of the research data analysis, several conclusions were obtained, namely, the academic information system running in universities has not met expectations. The performance of academic information systems that can support the smooth operation of the universities is not well understood. It is necessary to formulate an optimal academic information system strengthening strategy that can support the smooth operation of the universities.